Counselling psychology in South Africa: Relevance, crossroads, or service road? - Moodley, Prevan (PINS-Psychology in Society, 2022)
In the past decade, debates about the place of counselling psychology in South Africa escalated beyond academia to enter public, government, and juridicial spaces. These debates reappeared after amendments to the 1974 Health Professions Act had introduced scopes of practice in 2011. However, this scope-wars phase ended in the regulatory domain in 2019 when The Minister of Health gave notice not to proceed with the regulations. This followed after public comments and after the regulatory body set up processes to respond to both professional debates and a court judgement. This paper reviews this scope-wars phase and critically analyses the ways in which the professional vitality of counselling psychology was positioned. To do this I analyse the discursive frame of relevance and the trope of crossroads, asking how the crossroads was a professional cul-de-sac in disguise. I present an alternative discourse to consider a new route that can be chartered and built through transforming identities, ideologies, training, and practice. A service road metaphor is suggested as the alternative to show the value of counselling psychology practice in South Africa.